Analisis Kuat Tekan, Kuat Belah, dan Kuat Lentur Beton Menggunakan Limestone dan Bestmittel Sebagai Bahan Tambah - Juanito Eka Setiawan; Ricky Muhammad; Antonius Antonius (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of adding limestone and bestmittel on the compressive strength, splitting tensile strength, and flexural strength of concrete as an effort to improve the mechanical properties of concrete. The study employed a laboratory experimental method using test specimens in the form of concrete cylinders and beams consisting of normal concrete, variations with 10% limestone and 0.25% bestmittel, and 10% limestone and 0.5% bestmittel. Testing was conducted at 7 and 28 days of age through compressive strength, split tensile strength, and flexural strength tests. The results showed that the addition of limestone and bestmittel was able to improve concrete performance in certain mixtures. The highest compressive strength value was obtained in the 10% limestone and 0.25% bestmittel mixture, at 25.370 MPa at 28 days of age. Split tensile strength and flexural strength tests showed optimal results in the 10% limestone and 0.5% Bestmittel mixture, with split tensile strength of 2.205 MPa and flexural strength of 2.951 MPa. The addition of limestone and Bestmittel was proven to increase mixture density, improve workability, and enhance the mechanical quality of the concrete.